Injury epidemiology in Australian women's professional football - Garrett, L.; Donna, L.; Jones, M.; Whalan, M.; Duffield, R. (Journal of Science and Medicine in Sport, 2024)
Objective To describe the injury epidemiology of the Australian women's professional football (soccer) league (A-League W) over 7 consecutive seasons.